1999
DOI: 10.1038/sj.bjp.0702424
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1α and tumour necrosis factor‐α modulate airway smooth muscle DNA synthesis by induction of cyclo‐oxygenase‐2: inhibition by dexamethasone and fluticasone propionate

Abstract: 1 Previous studies have established that glucocorticoids inhibit airway smooth muscle DNA synthesis. The eects of a combination of the pro-in¯ammatory cytokines, interleukin-1a (IL-1a) and tumour necrosis factor-a (TNF-a) on the inhibition of DNA synthesis by glucocorticoids in human cultured airway smooth muscle have now been investigated, since these cytokines are chronically expressed in asthmatic airways. 2 Thrombin (0.3 u ml 71 ) and basic ®broblast growth factor (bFGF, 300 pM) stimulated increases in DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Airway smooth muscle (ASM) has now been recognized as a novel player in the pathogenesis of asthma (3,4) and might therefore be expected to be a prominent therapeutic target for inhaled steroids (5). In line with this, we and others showed that GCs were effective in abrogating the expression of a number of pro-inflammatory mediators including cytokines, chemokines, and adhesion molecules in ASM cells (5)(6)(7)(8)(9)(10).…”
supporting
confidence: 53%
“…Airway smooth muscle (ASM) has now been recognized as a novel player in the pathogenesis of asthma (3,4) and might therefore be expected to be a prominent therapeutic target for inhaled steroids (5). In line with this, we and others showed that GCs were effective in abrogating the expression of a number of pro-inflammatory mediators including cytokines, chemokines, and adhesion molecules in ASM cells (5)(6)(7)(8)(9)(10).…”
supporting
confidence: 53%
“…Multiple cytokines have been demonstrated to alter COX-2 expression in vitro. Proinflammatory cytokines including TNF-␣ (13,14), IL-1␣ (14,15), and IFN-␥ (16,17) have been demonstrated to induce COX-2 expression, whereas antiinflammatory cytokines such as IL-4 (18), IL-13 (19,20), and IL-10 (21) can inhibit COX-2 induction. The pleiotropic cytokine TGF-␤ can enhance (22) or inhibit (23) COX-2 expression, depending upon the cell type tested.…”
Section: Il-10 Is a Central Regulator Of Cyclooxygenase-2 Expression mentioning
confidence: 99%
“…For the HPLC assay of eicosanoids, spleen cell cultures were incubated for 30 min at 37°C with up to 7.5 M [5,6,8,9,11,12,14, H]arachidonic acid (AA) (155 Ci/mmol; New England Nuclear, Boston, MA) in serumfree medium. After incubation, the medium was collected and centrifuged to remove cellular debris.…”
Section: Hplcmentioning
confidence: 99%
“…First, the effects of GC seem to be highly gene-specific. For example, reports showed that dexamethasone can effectively inhibit cytokine-induced IL-6, RANTES (Ammit et al, 2002), eotaxin (Pang and Knox, 2001), or cyclooxygenase-2 expression (Vlahos and Stewart, 1999), whereas it has no effect on cytokine-induced ICAM-1 expression (Amrani et al, 1999). Second, GC suppressive effect seems to be time-dependent, because dexamethasone partially abrogates cytokine-mediated ICAM-1 expression at early time points but has no effect at later time points (Amrani et al, 1999).…”
mentioning
confidence: 99%